Customs Valuation in India: Identifying Trade Facilitation related Concerns - Sachin Chaturvedi (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
India has introduced several trade facilitation related measures in the last couple of years. The pro-active strategy adopted by the Central Board of Excise and Customs (CBEC) has helped in introducing several policy measures which have not only streamlined the role of the customs department but has also helped industry in a major way without compromising collection of revenue.
Keywords: F1; 330; Trade Facilitation; Customs Valuation; India